Do isolated calf deep vein thrombosis need anticoagulant treatment? - Palareti, Gualtiero (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Isolated calf deep vein thrombosis (ICDVT), defined as thrombosis confined to the infra-popliteal veins of the lower limbs, is a frequent finding in symptomatic out- and in-patients when the ultrasound examination is extended to the whole deep leg veins. Studies based on a complete investigation of deep veins in the whole leg, reported a prevalence of ICDVT of 7–11% in cases with suspected PE, 4–15% in cases with suspected DVT, and 23–59% in patients with diagnosis of DVT (1).